2015
DOI: 10.1371/journal.pone.0119737
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Immune Characterization of Mycobacterium abscessus Infection in Cystic Fibrosis Patients

Abstract: Cystic fibrosis patients are highly susceptible to infections with non-tuberculous mycobacteria. Especially Mycobacterium abscessus infections are common but reliable diagnosis is hampered by non-specific clinical symptoms and insensitive mycobacterial culture. In the present study we established novel methods for rapid detection and immune characterization of Mycobacterium abscessus infection in cystic fibrosis patients. We performed Mycobacterium abscessus specific DNA-strip- and quantitative PCR-based analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Similarly, mice or guinea pigs infected with aerosolized MAB exhibit an early influx of IFN-γ+ T cells preceding successful clearance (48). Further studies have shown that depletion of CD4 T cells or neutralization of IFN-γ causes worsening of MAC and MAB infection in mice (4951). Control of MAC and MAB infection also requires other key cytokines such as TNF-α and IL-12 (49, 5254).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mice or guinea pigs infected with aerosolized MAB exhibit an early influx of IFN-γ+ T cells preceding successful clearance (48). Further studies have shown that depletion of CD4 T cells or neutralization of IFN-γ causes worsening of MAC and MAB infection in mice (4951). Control of MAC and MAB infection also requires other key cytokines such as TNF-α and IL-12 (49, 5254).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we dissect faults in immunity in two cohorts of patients (CF and elderly) with NTM lung infection and matched controls to identify the underlying blood immune signatures of each disease. Blood was examined given: (i) T cells are known to traffic between the blood and lung ( 36 ); (ii) NTM-specific T cells have been observed in the blood ( 37 ); and (iii) blood is easy to access for diagnostic tests. The first cohort included CF patients with active NTM disease, CF patients with past NTM disease who had been successfully treated and were now in disease remission, CF patients with chronic Pa infection who had no history of NTM infection and a group of matched healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced Th1 and Th2 cell immune responses associated with upregulated Th17 response have been reported in patients with MAbsC pulmonary disease compared to healthy controls [26]. In a small study of CF patients, an increased frequency of antigen-specific peripheral blood T cells expressing CD40L(+) but not IL-2(−) was found mostly in patients with MAbsC pulmonary disease [27]. This limited immune profiling information suggests that MAbsC infections are associated with alterations in some specific pathways of cell-mediated immunity that may contribute to disease progression.…”
Section: Risk Factorsmentioning
confidence: 99%